2016
DOI: 10.1021/acs.inorgchem.6b00267
|View full text |Cite
|
Sign up to set email alerts
|

Stable Alkali-Metal Complexes of Hybrid Disila-Crown Ethers

Abstract: The complexation ability of hybrid disilane and ethylene containing crown ether ring systems was analyzed using 1,2-disila[12]crown-4 (1), 1,2-disila[15]crown-5 (2), 1,2-disila[18]crown-6 (3), and 1,2,7,8-tetrasila[12]crown-4 (7). Alkali-metal complexes (Li(+), Na(+), K(+)) were obtained and analyzed via X-ray diffraction. The complex stability of [Li(1,2-disila[12]crown-4)](+) and [Li(1,2,7,8-tetrasila[12]crown-4)](+) was determined, in relation to the lithium complex of [12]crown-4, by density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
95
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(104 citation statements)
references
References 28 publications
7
95
0
2
Order By: Relevance
“…Prior studies have shown that Li + matches well with 1,2-disila [12]crown-4 and Na + with 1,2-disila [15]crown-5 [18], so that the two cations together with 1,2-disila [18]crown-6 are supposed to fulfil the criteria of a mismatch. Reaction of 1,2-disila [18]crown-6 with lithium hexafluorophosphat in a 1:1 stoichiometry yielded a highly viscous oil. After freezing at −196 • C and subsequent storage at −35 • C for 3 days, Compound 1 crystallized in the space group P2 1 /c in the form of colorless planks.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Prior studies have shown that Li + matches well with 1,2-disila [12]crown-4 and Na + with 1,2-disila [15]crown-5 [18], so that the two cations together with 1,2-disila [18]crown-6 are supposed to fulfil the criteria of a mismatch. Reaction of 1,2-disila [18]crown-6 with lithium hexafluorophosphat in a 1:1 stoichiometry yielded a highly viscous oil. After freezing at −196 • C and subsequent storage at −35 • C for 3 days, Compound 1 crystallized in the space group P2 1 /c in the form of colorless planks.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, higher comparability between organic crown ethers and cyclosiloxanes can be provided by extension of the -SiMe 2 -unit to -SiMe 2 SiMe 2 -. Recent studies of hybrid [12]crown-4 featuring one or two disilane fragments in a residuary organic crown ether framework revealed an increasing coordination ability towards Li + in the series C-O-C < C-O-Si < Si-O-Si (Scheme 1) [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations